1970
DOI: 10.1161/01.cir.41.4.605
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Chamber Volume, Mass, and Function in Severe Coronary Artery Disease

Abstract: Twenty-three patients, 15 of whom had clinical and electrocardiographic evidence of previous myocardial infarction, were studied by coronary arteriography and biplane angiocardiography. End-diastolic volume ranged from 55 to 317 ml/m 2 , left ventricular mass from 83 to 294 g/m 2 and ejection fraction from 0.13 to 0.75. An increased enddiastolic volume was associated with an increased left ventricular mass (r = 0.77, P < 0.01). In 15 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0

Year Published

1973
1973
1996
1996

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 15 publications
4
4
0
Order By: Relevance
“…Further errors may result both from attenuation of counts from regions of the left ventricle most distant from the probe during ventricular dilatation, as well as from changes in background counts during exercise. Moreover the left ventricular volumes cal-culated at rest and during dynamic exercise in the present series were similar to those derived by conventional gamma camera and biplane cineangiography techniques in patients with equivalent coronary artery disease (Rackley et al, 1970;Feild etal., 1972;Links etal., 1982;McKay etal., 1984). An increased pulmonary blood flow during exercise would be expected to increase background activity; indeed Okada et al (1980) have demonstrated that lung activity increases as left ventricular filling pressure rises.…”
Section: Resultssupporting
confidence: 83%
“…Further errors may result both from attenuation of counts from regions of the left ventricle most distant from the probe during ventricular dilatation, as well as from changes in background counts during exercise. Moreover the left ventricular volumes cal-culated at rest and during dynamic exercise in the present series were similar to those derived by conventional gamma camera and biplane cineangiography techniques in patients with equivalent coronary artery disease (Rackley et al, 1970;Feild etal., 1972;Links etal., 1982;McKay etal., 1984). An increased pulmonary blood flow during exercise would be expected to increase background activity; indeed Okada et al (1980) have demonstrated that lung activity increases as left ventricular filling pressure rises.…”
Section: Resultssupporting
confidence: 83%
“…Since ejection fraction is the ratio of stroke volume to end-diastolic volume, left ventricular end-diastolic volume index can be derived from simultaneously measured stroke volume index and ejection fraction. It appears that the left ventricular volume calculated at rest and during dynamic exercise in the present series were similar to those derived by conventional gammacamera and biplane cineangiography techniques in patients with equivalent coronary artery disease (Links et al, 1982;Rackley et al, 1970;Feild et al, 1972;McKay et al, 1984).…”
Section: Discussionsupporting
confidence: 76%
“…Subgroup analysis ofpatients without LVH according to mass criteria Among patients without LVH 12/21 (57%) showed LV concentric remodelling (LVCR) (relative wall thickness > 0A45) and 9/21 (43%) did not. Patients without LVCR were younger than those with LVH and those with LVCR (52 (23) v 65 (14) and 64 (19) years, respectively, P < 0 05). The interval since diagnosis of aortic stenosis was 3-2 (6 2) years in patients without LVCR and 8&2 (6-1) years in patients with LVCR (P < 0-05).…”
Section: Multivariate Analysismentioning
confidence: 88%